ABUSE, REUSE, RECYCLE: THE USES OF BASALT ORTHOSTATS AT HAZOR IN THE BRONZE AND IRON AGES. Issue 1 (19th January 2021) - Bechar, Shlomit
Summary: This paper investigates the use of basalt orthostats in Syro‐Anatolia throughout the Bronze and Iron Ages, focusing on the changes in their consumption at Hazor. Used to reflect the wealth and power of city rulers in the Middle and Late Bronze Ages, this practice continued in the Iron Age in Syro‐Anatolia, while at Hazor it stopped entirely. By applying the modern concepts of counter‐monumentality and spolia, it is suggested that, at Hazor, the orthostats were used by the Iron Age inhabitants of the city to glorify the destruction of the Late Bronze Age city and to humiliate the previous royalty of Hazor, thus exhibiting their victory over its Canaanite rulers.